THE ROLE OF FAMILY AND INSTITUTIONAL PARTNERSHIPS IN DEVELOPING SOCIAL-EMOTIONAL SKILLS IN PRESCHOOL CHILDREN (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the role of family and institutional partnerships in developing social-emotional skills in preschool children. Social-emotional development plays a critical role in shaping a child's ability to form positive relationships, regulate emotions, express empathy, and adapt to different social contexts. The study highlights the importance of consistent collaboration between parents, educators, and early childhood education institutions in promoting emotional stability and social competence. Emphasis is placed on the need for coordinated efforts to create supportive environments where children can thrive emotionally and socially. Practical recommendations are provided for strengthening family-institution cooperation to enhance children's holistic development.